KEABSAHAN SURROGATE MOTHER TERHADAP STATUS KEPERDATAAN ANAK : Studi Perbandingan Surrogate Mother Di Indonesia Dan Ukraina - Adinda Permana Putri (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2021)
Nowadays technology is getting more advanced. Among them is "in vitro fertilization (IVF)" with the help of a surrogate mother. The Surrogate Mother is a woman who has absolutely nothing to do with the husband and wife who owns the seeds and then makes an agreement or agreement with the husband and wife to rent out her womb in exchange for ordinary things. This paper aims to determine the validity of surrogate mothers in Indonesia and the validity of surrogate mothers in Ukraine regarding the civil status of children born using normative juridical research methods. And the result of this research is that in Indonesia Surrogate Mother are not allowed because it is against the existing law in Indonesia, especially in Article 127 of Law Number 36 Year 2009 which prohibits the existence of a surrogate mother agreement and if a child is born. to the surrogate mother, then the child is born to the surrogate mother. Meanwhile in Ukraine, surrogate mother is legalized under Article 123 of the Family Code of Ukraine 2002 and the civil status of the child is a genetic descendant of a married couple who have seeds.